Fixed-time formation fault tolerant control for unmanned surface vehicle systems with intermittent actuator faults - Wu, Wei; Tong, Shaocheng (Ocean engineering, 2023)
This article studies the fixed-time fuzzy formation tracking control problem for multiple unmanned surface vehicle (USV) systems with intermittent actuator faults. Since each USV is subject to unknown motion dynamics and the external disturbances. The fuzzy state observers are developed to estimate the positions and velocity in multiple USV systems, and disturbance observers are developed to estimate the external disturbances, and fuzzy logic systems are utilized to identify the unknown motion dynamics. Then, to compensate for the influence of intermittent actuator faults, the novel fixed-time adaptive output-feedback formation fault-tolerant controllers are constructed by constructing the integral type Lyapunov function and co-designing the last virtual controller. The presented formation control method can guarantee all the signals in multiple USV systems are bounded in fixed-time. Finally, simulation results and comprehensive comparisons are provided to verify the effectiveness of the presented formation control method. •This paper proposes an observer-based fuzzy formation FTC approach for multiple nonlinear USV systems. The presented formation FTC can achieve to compensate for the influence of IAFs. Although the recent works (Wang, 2021; Zhang et al., 2022) also address the FTC problem for nonlinear USVs, their FTC method only deal with a finite of actuator fault and can not be applied to control nonlinear multiple USV systems with immeasurable states in this study.